Numeracy and literacy skill in elementary school students: The utilization of kampus mengajar perintis program - Hendrowati, Tri Yuni; Sunanto, Rahma Faelasofi (Desimal: Jurnal Matematika, 2021)
Numeracy and literacy skill is some of the current demands that are expected to be the competencies that students have. The purpose of this research is to find out the numeracy and literacy skills of elementary school students before and after receiving periodic assistance on the Kampus Mengajar Perintis program. Sampling was done by using the saturated sampling technique. The research instrument used was problems derived from the literacy and numeracy modules of the elementary school level. The data analysis technique used the paired t-test because the population research data were normally distributed. The result of this research is that the literacy ability of elementary school students has increased with the acquisition of an average score of 8.47. It is higher than before getting the treatment of the Kampus Mengajar Perintis program which is 7.25. Then, the numeracy ability of elementary school students has increased with the acquisition of an average score of 8.16. It is higher than before getting the treatment of the Kampus Mengajar Perintis program which is 6.